Hinokiflavone Inhibits Growth of Esophageal Squamous Cancer By Inducing Apoptosis via Regulation of the PI3K/AKT/mTOR Signaling Pathway - Guo, Jida; Zhang, Shengqiang; Wang, Jun; Zhang, Pengfei; Lu, Tong; Zhang, Linyou (Frontiers in Oncology, 2022)
Background: Globally, esophageal cancer ranks the seventh most common cancer. Esophageal squamous cell carcinoma (ESCC) is one of its major histological types. ESCC accounts for the vast majority of cases in China, and the mortality rate is high. Cisplatin, the standard adjuvant chemotherapy drug for ESCC, has a modest response rate due to the development of drug resistance. Hinokiflavone (HF) is a natural biflavonoid compound with anti-melanoma activity. However, its anti-tumor effects on ESCC and the underlying mechanisms remain largely unknown. Methods: The ESCC cell lines KYSE150 and TE14 were used. Cell counting kit-8 and flow cytometry analysis, along with colony formation, EdU, wound healing, and Transwell migration assays, were performed to assess cell characteristics (viability, migration, invasion, and apoptosis) following treatment with HF. Gene Ontology (GO), Kyoto Encyclopedia of Genes and Genomes (KEGG), western blotting, and molecular docking were used to investigate the pathways potentially modulated by HF. In vivo anti-tumor effects of HF were also investigated using a mouse xenograft model. Results: Our findings revealed that HF inhibited ESCC cell proliferation. Hoechst 33342 staining, annexin V-FITC/PI staining and western blotting confirmed that HF could cause caspase dependent apoptosis. KEGG pathway enrichment analysis and western blotting indicated that the PI3K/AKT/mTOR pathway played an important role in the process of HF induced apoptosis. Furthermore, HF effectively impaired the migration and invasion abilities of KYSE150 cells and downregulated the expression of the matrix metalloproteinases (MMP) MMP2 and MMP9. HF inhibited tumor growth and exhibited minimal toxicity in the organs of the KYSE150 xenograft model. Conclusion: This is the first study to demonstrate the inhibition of ESCC growth and progression by HF. The underlying mechanism is through blocking the PI3K/AKT/mTOR signaling pathway thereby inhibiting cell proliferation and inducing apoptosis. HF can be used as a complementary/alternative agent for ESCC therapy.